The effect of gender role orientation on work interference with family (WIF) and family interference with work (FIW) among married female nurses in Shiraz-Iran. - Namayandeh, Hajar; Yaacob, Siti Nor; Juhari, Rumaya (Canadian Center of Science and Education, 2010)
The present study highlights the significance of gender role orientation as one of the most important individual factors on WIF and FIW. Furthermore, this paper also examines the effects of some of the essential personal backgrounds such as age, job experience and duration of marriage on WIF and FIW. This study consists of 198 married female nurses in Shiraz-Iran. The findings re vealed that married female nurses who adopt more egalitarian gender role attitude are associated with high er WIF. Unlike previous studies, the finding also indicates that respondents who adopt a more egalitarian gender role attitude experienced higher FIW, which may be explained by the specific cultural context in Iran. This study also established that female nurses with older age, more years of job experience, and longer duration of marriage, perceived lower level of WIF and FIW. Implications are discussed and recommendations are ma de regarding future researches in this area.